2023
DOI: 10.3390/pr11020359
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Wetlands in Mexico for Control of Wastewater Contaminants: A Review of Experiences during the Last Twenty-Two Years

Abstract: Constructed or treatment wetlands (CWs) are a sustainable option to clean wastewater in the face of water pollution problems. Consequently, this study was aimed at reviewing and analyzing the use of CWs in Mexico. This involved types, sizes, and functionality in the removal of pollutants, as well as the main plant species that are used. Furthermore, 67 studies regarding CWs were found, which were classified according to the treatment area as microcosms, mesocosms, pilot scale, and full-scale at 18, 30, 25, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Constructed Wetlands (HC) are eco-technologies that have been recognized as reliable alternatives to reduce the problem of effluent pollution from domestic wastewater, agricultural waste, industrial waste, runoff and leachate from landfills, these systems have been reported as effective in removing contaminants (BOD5 and STD), with characteristics that make their construction even more striking, such as the low economic investment requirement, low maintenance cost, minimal or no energy cost and That is why they are having success in various parts of the world, considering their climate, vegetation and substrate important for their construction [26]. Recently reported as efficient in the removal and/or retention of Microplastics with a rate of 88.63% in Subsurface Flow Constructed Wetlands (SF-CW) [27]; and with an efficiency of up to 98.13% with Wetlands Built with horizontal flow as a third treatment after having passed through a biological reactor [25] in addition to this type of Wetlands being the most commonly used [28], conditioned with plants with ornamental flowers, that key elements in the removal efficiency of common contaminants in domestic wastewater are also reported [29]. Reasons why, it was considered appropriate to adapt a system of Constructed Subsurface Flow Wetlands conditioned with ornamental plants for the experiment; Two different types, Hippeastrum Hybridum hort and Heliconia bihai marginata, were used because they are native to subtropical and tropical regions, such as Misantla, which makes their access easy if replacement is necessary during the adaptation period (four weeks) or later.…”
Section: Methodsmentioning
confidence: 99%
“…Constructed Wetlands (HC) are eco-technologies that have been recognized as reliable alternatives to reduce the problem of effluent pollution from domestic wastewater, agricultural waste, industrial waste, runoff and leachate from landfills, these systems have been reported as effective in removing contaminants (BOD5 and STD), with characteristics that make their construction even more striking, such as the low economic investment requirement, low maintenance cost, minimal or no energy cost and That is why they are having success in various parts of the world, considering their climate, vegetation and substrate important for their construction [26]. Recently reported as efficient in the removal and/or retention of Microplastics with a rate of 88.63% in Subsurface Flow Constructed Wetlands (SF-CW) [27]; and with an efficiency of up to 98.13% with Wetlands Built with horizontal flow as a third treatment after having passed through a biological reactor [25] in addition to this type of Wetlands being the most commonly used [28], conditioned with plants with ornamental flowers, that key elements in the removal efficiency of common contaminants in domestic wastewater are also reported [29]. Reasons why, it was considered appropriate to adapt a system of Constructed Subsurface Flow Wetlands conditioned with ornamental plants for the experiment; Two different types, Hippeastrum Hybridum hort and Heliconia bihai marginata, were used because they are native to subtropical and tropical regions, such as Misantla, which makes their access easy if replacement is necessary during the adaptation period (four weeks) or later.…”
Section: Methodsmentioning
confidence: 99%
“…During the twentieth and twenty-first centuries, the loss of natural wetlands ranged from 64% to 71% [86]. Thus, the governments of the world should support and encourage the creation of CWs, especially for the treatment of municipal waters in developing countries [87].…”
Section: Political Positionsmentioning
confidence: 99%
“…By releasing oxygen in their root zone, plants favor the development of aerobic microzones that enable the processes of pollutant removal. They also directly participate in the uptake of different components such as nutrients [6,7]. Therefore, the selection and use of plants are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…are commonly used worldwide in CWs for wastewater treatment On the other hand, ornamental plants have also been studied in tropical and subtropical regions due to their ability to adapt to the prevailing conditions in the different types of CWs. The presence of ornamental species increases the attractiveness of CWs and can also contribute to better efficiency of these systems in the removal of pollutants [6,10]. Regarding the filter media used in CWs, gravel and sand are the most common ones [4]; however, other alternatives such as biochar have been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation